1984
DOI: 10.1007/bf00313940
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and localizing significance of motor and sensory electroneurographic parameters in the diagnosis of ulnar nerve lesions at the elbow

Abstract: A total of 103 patients (40 with pure sensory disturbances, 63 with sensory and motor deficits) with ulnar nerve lesions at the elbow were examined neurophysiologically. The measurement of motor conduction velocity across the cubital tunnel alone did not completely localize the lesion. The latency to an ulnar-innervated flexor muscle was of outstanding importance. The measurement of amplitudes was only rarely of localizing significance. The results of sensory recording proved to be important in patients with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
1
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 17 publications
3
28
1
1
Order By: Relevance
“…Bielawski and Hallett 2 found that with the elbow flexed, the yield of absolute acrosselbow MNCV was 40% and of relative slowing was 25%. Tackmann et al 14 found that among patients with both sensory and motor involvement clinically, 65% had elbow slowing and only 49% localized to the elbow by slowing relative to the forearm. However, Kothari and Preston 8 identified 100% of their patients by slowing in elbow segment relative to forearm segment and were able to identify only 80% by absolute across-elbow MNCV slowing.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Bielawski and Hallett 2 found that with the elbow flexed, the yield of absolute acrosselbow MNCV was 40% and of relative slowing was 25%. Tackmann et al 14 found that among patients with both sensory and motor involvement clinically, 65% had elbow slowing and only 49% localized to the elbow by slowing relative to the forearm. However, Kothari and Preston 8 identified 100% of their patients by slowing in elbow segment relative to forearm segment and were able to identify only 80% by absolute across-elbow MNCV slowing.…”
Section: Discussionmentioning
confidence: 98%
“…1,2,[5][6][7][8]14 Some authors have reported a higher sensitivity for identifying UNE by the detection of absolute slowing of conduction velocity in the elbow segment, that is, when conduction velocity drops below a reference value such as 50 m/s. 2,5,14 Others have noted that to localize an ulnar neuropathy to the elbow, the motor conduction velocity across the elbow must be disproportionately slower than the velocity of an adjacent nerve segment. 6 -8 In addition, the usefulness of nerve conduction velocity comparison between the across-elbow and forearm segments is unclear if the presence of significant axonal loss causes loss of faster fibers.…”
mentioning
confidence: 98%
“…19,22 The precise separation of the cubital tunnel syndrome from the epicondylar compression is important in determining therapeutic strategy. 7 This distinction was solely achieved by the short-segmental motor nerve conduction technique (inching technique).…”
Section: Discussionmentioning
confidence: 99%
“…8,15,16 The precise location of the lesion in ulnar neuropathy at the elbow is usually indicated by the motor NCS (in an average 67% of cases in seven series). 1,11,[17][18][19][20][21][22] In the past, the motor nerve conduction technique was preferred; sensory and mixed nerve conduction recordings across the elbow with surface electrodes was not used until recently. 18 Sensory and mixed NCS with surface electrodes suggested an elbow lesion in 73% of cases in one study by demonstrating abnormal sensory and mixed NCS below the elbow.…”
Section: Discussionmentioning
confidence: 99%
“…4 Its electrophysiological recognition depends on motor nerve conduction velocity measurements across this segment. The length of this ulnar nerve segment is generally determined by measuring the distance from stimulation points below to above the elbow with the elbow in flexion.…”
mentioning
confidence: 99%